The Colloidal Stabilization of Carbon with Carbon: Carbon Nanobubbles as both Dispersant and Glue for Carbon Nanotubes1. Issue 4 (5th December 2013) - Kuzmicz, Danuta; Prescher, Simon; Polzer, Frank; Soll, Sebastian; Seitz, Christoph; Antonietti, Markus; Yuan, Jiayin
Abstract The superior physical properties of carbon nanotubes (CNTs) have led to their broad application. Intrinsically, CNTs tend to agglomerate from hydrophobic interactions, which is highly undesirable for solution processing and device fabrication. Commonly, a stabilizer consisting of organic surfactants or polymers is used to disperse CNTs. Recently, we synthesized nitrogen‐doped carbon hollow nanospheres (25–90 nm), termed carbon "nanobubbles". They bear superior dispersability in water and distinctive graphitic order. Herein, we describe the nanobubble‐assisted dispersion of CNTs in aqueous solution upon sonication. This process relies on the π–π interaction between the two aromatic carbon nanostructures, which can process their carbon mixture in water into conductive filter membranes, ink, and discs. This stabilization can be extended to other aromatic carbons. In addition, the π–π interaction may create a new type of carbon p–n junction that can be used to improve charge separation.